Website Aesthetics and Technology Playfulness in Encouraging Customer Use of Online based Self-Service Technologies: Special Reference to Commercial Banks in Sri Lanka - Galdolage, Sandamali; Rasanjalee, Samudrika (Advances in Technology, 2022)
Rapid technological advancements have aided the service sector's continued evolution, converting traditional physical service encounters managed by service professionals into self-service technologies (SSTs) controlled by customers. Despite the fact that prior studies have attempted to understand customers' technology acceptance in general, sufficient attention has not been paid to the study of self-service technologies, particularly Online based SSTs. Hence, the purpose of this study is to investigate the website aesthetics and technology playfulness of online-based SSTs leading the use of self-service technologies in the Sri Lankan commercial banking industry. A qualitative approach was undertaken, conducting 50 semi-structured interviews with banking customers who use SSTs in the Western Province, Sri Lanka with the use of a non-probabilistic purposeful sampling strategy. The method of thematic analysis was used to analyze the data. The findings revealed “Information quality and guidance”, “Innovative systems and facilities”, “Use of multiple languages”, “High interactivity” and “Visually appealing techniques” as the five themes of website aesthetics and “Enjoyment”, “Exciting”, “Entertaining”, “Creativity”, “Delight” and “Appealing features” as the six themes of technology playfulness leading towards the use of online-based SSTs in the banking sector. The findings would occupy the vacuum of existing literature on the customer use of online-based self-service technologies. Practitioners will be given direction with the understanding on how consumers could be encouraged towards the use of online-based SSTs with the integration of website aesthetics and technology playfulness to improve the delivery of self-service technologies in the commercial banking sector.